Rhabdoid Meningioma of Brain - A Rare Aggressive Tumor - Mondal, Sajeeb (Indian J Med Paediatr Oncol, 2017)
Rhabdoid meningioma is a rare aggressive variant of meningioma, regarded as WHO Grade III type. Histologically and cytologically, it is distinctive type having abundant eosinophilic cytoplasm, cytoplasmic inclusion with eccentrically placed vesicular nuclei and prominent nucleoli. High recurrence rate and poor outcome are important features. Here, we are presenting a rare case of rhabdoid meningioma found in a recurrent meningioma of the posterior fossa in a middle-aged female. We emphasized the squash cytology and histology finding of the rare neoplasm.